2017
DOI: 10.1002/lary.26773
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of medialization laryngoplasty with and without arytenoid adduction

Abstract: 4. Laryngoscope, 127:2591-2595, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…McCulloch et al evaluated voice outcomes in patients who underwent ML alone versus ML+AA and demonstrated greater improvement in multiple voice parameters in the ML+AA group; however, no statistical comparisons were made between the two treatment groups. 48 Although Chang et al 49 demonstrated that both ML and ML+AA resulted in improvement in overall severity voice scores based on the CAPE-V perceptual evaluation tool, the difference in overall severity was not statistically significant at any time point between the two treatment groups. 49 Our study also found that both ML and ML+AA resulted in improved overall CAPE-V scores, although difference in improvement between groups was not significant after adjusting for covariates.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…McCulloch et al evaluated voice outcomes in patients who underwent ML alone versus ML+AA and demonstrated greater improvement in multiple voice parameters in the ML+AA group; however, no statistical comparisons were made between the two treatment groups. 48 Although Chang et al 49 demonstrated that both ML and ML+AA resulted in improvement in overall severity voice scores based on the CAPE-V perceptual evaluation tool, the difference in overall severity was not statistically significant at any time point between the two treatment groups. 49 Our study also found that both ML and ML+AA resulted in improved overall CAPE-V scores, although difference in improvement between groups was not significant after adjusting for covariates.…”
Section: Discussionmentioning
confidence: 91%
“…Chang et al determined that the posterior gap showed improved closure only in the ML+AA group compared to ML alone. 49 Abraham et al reported that ML+AA appeared to show improved closure of the posterior glottis, with no difference in complication rates, when compared to ML alone. 28 Our study also found no significant increase in total complications, defined as postoperative hematoma, vocal fold edema, wound infection, or tracheostomy, with ML+AA compared to ML alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is no recovery or if there is inadequate compensation after UVFP, procedures aiming to restore glottic competence include permanent and temporary vocal fold injections or laryngeal framework surgery, such as a type I medialization laryngoplasty. Relatively small glottic gaps between membranous vocal folds are generally accepted to be more appropriate for injection laryngoplasty, whereas larger glottic gaps with symptomatic posterior glottic gaps are found to be ideal for medialization laryngoplasty with or without the addition of an arytenoid adduction …”
Section: Introductionmentioning
confidence: 99%